2014
DOI: 10.1124/dmd.114.059709
|View full text |Cite
|
Sign up to set email alerts
|

Endoxifen and Other Metabolites of Tamoxifen Inhibit Human Hydroxysteroid Sulfotransferase 2A1 (hSULT2A1)

Abstract: Although tamoxifen is a successful agent for treatment and prevention of estrogen-dependent breast cancer, its use has been limited by the low incidence of endometrial cancer. Human hydroxysteroid sulfotransferase 2A1 (hSULT2A1) catalyzes the formation of an a-sulfooxy metabolite of tamoxifen that is reactive toward DNA, and this has been implicated in its carcinogenicity. Also, hSULT2A1 functions in the metabolism of steroid hormones such as dehydroepiandrosterone (DHEA) and pregnenolone (PREG). These roles o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 59 publications
(68 reference statements)
2
20
0
Order By: Relevance
“…The enzymatic reactions were analyzed by LC-MS, and the negative ion ESI-MS of the products formed by the hSULT1A1*1-catalyzed sulfation of 4-OHTAM, endoxifen, and N-desTAM (Supplemental Figs. 8-10, respectively) were similar to previous ESI-MS data from reactions catalyzed by hSULT2A1 (Squirewell et al, 2014). The retention times of 4-TAM-SO 4 , endoxifensulfate, and N-desTAM-S on LC-MS chromatography (data not shown) were 16.30, 16.07, and 21.81 minutes, respectively.…”
Section: Inhibition Of Hsult1e1-catalyed Sulfation Of Estradiol By Mesupporting
confidence: 75%
See 3 more Smart Citations
“…The enzymatic reactions were analyzed by LC-MS, and the negative ion ESI-MS of the products formed by the hSULT1A1*1-catalyzed sulfation of 4-OHTAM, endoxifen, and N-desTAM (Supplemental Figs. 8-10, respectively) were similar to previous ESI-MS data from reactions catalyzed by hSULT2A1 (Squirewell et al, 2014). The retention times of 4-TAM-SO 4 , endoxifensulfate, and N-desTAM-S on LC-MS chromatography (data not shown) were 16.30, 16.07, and 21.81 minutes, respectively.…”
Section: Inhibition Of Hsult1e1-catalyed Sulfation Of Estradiol By Mesupporting
confidence: 75%
“…Products of sulfation catalyzed by hSULT1E1 and hSULT1A1*1 were identified by liquid chromatography-mass spectrometry (LC-MS) analysis on a Waters Q-TOF Premiere mass spectrometer, as described previously (Squirewell et al, 2014). Briefly, each 50 ml reaction was performed at pH 7.4 and used 50 mM substrate with 50 mM PAPS in the presence of 0.25 M potassium phosphate, 8.3 mM 2-mercaptoethanol, and 2% ethanol (v/v).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tamoxifen citrate, as a first line of treatment for infertile men with idiopathic oligozoospermia, was proposed by the World Health Organization (WHO) Working Committee (Rowe et al, 2000). Tamoxifen undergoes extensive hepatic and gut wall metabolism in humans for several primary and secondary metabolites that exhibit a range of pharmacologic activity (Squirewell et al, 2014). Previous research demonstrated that endoxifen formation proceeds stepwise by oxidation of tamoxifen with N-desmethyltamoxifen (NDM) as the predominant intermediate (Desta et al, 2004), and patients receiving tamoxifen are influenced by cytochrome P4502D6 (CYP2D6) genetic variants (Stearns et al, 2003;Jin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%